2020
DOI: 10.3390/mi11030240
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Boundary-Driven Acoustic Streaming in Microfluidic Channels with Circular Cross-Sections

Abstract: While acoustic streaming patterns in microfluidic channels with rectangular cross-sections have been widely shown in the literature, boundary-driven streaming fields in non-rectangular channels have not been well studied. In this paper, a two-dimensional numerical model was developed to simulate the boundary-driven streaming fields on cross-sections of cylindrical fluid channels. Firstly, the linear acoustic pressure fields at the resonant frequencies were solved from the Helmholtz equation. Subsequently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Furthermore, the authors [36] showed that the temperature drop increases more than linearly with the increase of the temperature difference between the hot and cold surface. The authors of the work [37] have shown that streaming can occur not only in rectangular channels, but also in curved geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors [36] showed that the temperature drop increases more than linearly with the increase of the temperature difference between the hot and cold surface. The authors of the work [37] have shown that streaming can occur not only in rectangular channels, but also in curved geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The important key words of this study are “flow in microfluidic channel”, “vibration input”, “surfactant”, and “experiment”. However, there are many studies discussing the flow in a microfluidic channel through the use of a “simulation” [ 7 , 11 , 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The closest study from the viewpoint of overlapping key words is that conducted by Kelder et al, who discussed the mathematical formulation of a fluid flow by considering the “vibration input” and the “surfactant” and showed various interesting “numerical simulations,” while focusing on the behavior of droplets appearing from the membrane rather than those of the fluid flow [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The closest study from the viewpoint of overlapping key words is that conducted by Kelder et al, who discussed the mathematical formulation of a fluid flow by considering the “vibration input” and the “surfactant” and showed various interesting “numerical simulations,” while focusing on the behavior of droplets appearing from the membrane rather than those of the fluid flow [ 31 ]. Lei et al discussed the “numerical simulation” of a boundary-driven acoustic streaming based “vibration input” in microfluidic channels and demonstrated a standing wave generated by a harmonic vibration of the boundary vibration input, although the main target was not focused on a fluid flow [ 41 ]. Based on a survey of conventional studies, no simulations indicated by the three key phrases “flow in a microfluidic channel”, “vibration input”, and “surfactant” have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Circular cross-section glass capillaries have been widely used for acoustic concentration/focusing of microparticles. Typically, in such a device, a (1, 0) mode is generated in cross-section of the fluid channel where the primary and lateral acoustic radiation forces tend to move microparticles into the center of the channel [ 60 ]. An early relevant work was performed by Goddard and Kaduchak [ 61 ], who designed an acoustic microparticle focusing device that is composed of a circular cross-section glass capillary and a PZT, shown in Figure 9 A.…”
Section: Ultrasonic Particle Manipulation (Upm) In Glass Capillariesmentioning
confidence: 99%